Ответ:
Объяснение:
використовувалися спрощені формули множення
a³-b³=(a²+ab+b²)
(a-b)(a+b)=a²-b²
((a-b)²=a²-2ab+b²
d)x²-49=x²-7²=(x-7)(x+7)
e)16x²-8xy+y²=(4x-y)²=(4x-y)(4x-y)
f)27a³-8m³=(3a)³-(2m)³=(3a-2m)(9a²+6am+4m²)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Объяснение:
використовувалися спрощені формули множення
a³-b³=(a²+ab+b²)
(a-b)(a+b)=a²-b²
((a-b)²=a²-2ab+b²
d)x²-49=x²-7²=(x-7)(x+7)
e)16x²-8xy+y²=(4x-y)²=(4x-y)(4x-y)
f)27a³-8m³=(3a)³-(2m)³=(3a-2m)(9a²+6am+4m²)